Rainfall in Q.S. Al-Zukhrūf Verse 11 A Perspective from A.J. Ayer’s Verification Theory - Huda, Moh. Saiful; Husna, Ulfatul; Fadllurrahman, Moh.; Imtiyaz, Najib Asyrof (UIR Press, 2026)
This study aims to examine the semantic and philosophical implications of Q.S. al-Zukhrūf [43]: 11, which elucidates the phenomenon of precipitation, by employing the analytical framework of the philosophy of language, specifically A.J. Ayer’s verification principle. The primary objective of this research is to evaluate the logical and empirical validity of Qur’anic propositions regarding natural phenomena. This evaluation seeks to map the locus of religious language within the strict meaningfulness criteria delineated by logical positivism. Methodologically, this qualitative study applies tafsīr maudlū’ī (thematic exegesis) alongside an analytic philosophy approach. Ayer’s verification theory posits that a proposition is rendered meaningful solely if it is susceptible to empirical and logical verification. Within this context, the statements in Surah al-Zukhrūf verse 11 concerning the divinely ordained phenomenon of rainfall are evaluated regarding both their scientific and theological significance. The findings indicate that the verse possesses not only spiritual resonance but also empirical correspondence with modern scientific understandings of the hydrological cycle. From Ayer’s perspective, the semantic content of the verse is logically acceptable when construed as an observable and testable natural phenomenon, thereby fulfilling the criteria for “strong” verifiability. Specifically, the study demonstrates that the Qur’anic phrasing bi qadarin (in due measure) inherently contains robust “verifiability in principle.” This is due to its direct correlation with meteorological observational data, effectively shifting the epistemic status of the statement from a purely metaphysical assertion to a philosophically significant factual proposition. Ultimately, this study underscores the necessity of interdisciplinary approaches in interpreting cosmological verses, thereby facilitating a rigorous dialogue between divine revelation and modern philosophical discourse.